Nanocatalyst from waste for biodiesel production - Zik, Nor Azyan Farrah Adila; Sulaiman, Sarina; Jamal, Parveen (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Catalyst is a substance that enables chemical reaction in faster rate. In biodiesel production, catalyst plays as an important role as it can increase the reaction rate of the reaction. The types of catalyst that usually can be found are homogeneous and heterogeneous catalyst. However, homogenous catalyst is difficult to separate with the product (biodiesel) at the end of the reaction compared to heterogeneous catalyst which leads to production of high volume of waste water and having an issue in regeneration of the catalyst. In order to overcome these issues, many researchers study about heterogeneous catalyst for production of biodiesel. The heterogeneous catalyst can be developed from natural resources such as animal bone, waste and natural rock. In addition, the reaction rate of the catalyst also can be enhanced by using nanocatalyst due to high catalytic efficiency, large surface area, high resistance to saponification and good rigidity. Therefore, the rate of the reaction in biodiesel production can be enhanced by high catalytic activity of catalyst with higher surface area and the production cost can also be reduced by choosing the source of catalyst from waste.